Inibição da integrina αvβ3 em cultura celular 3D de células tumorais e endoteliais em ambiente hipóxico utilizando a desintegrina recombinante DisBa-01 - Baptista, Matheus Pintor (Universidade Federal de São Carlos, 2022)
Breast cancer has a high global incidence, it was the most fatal type of cancer in 2020, When 66,280 new cases were estimated just in Brazil. The main problems associated with tumors are related to their metastatic behavior, that is, their ability to migrate and get in secondary tissues. This process takes place through the extracellular matrix and is supported by angiogenesis, relying on the mediation of cell ligands called integrins. Simulating the tumor microenvironment in vitro allows the understanding of cell signaling processes, which can be done by 3D culture. Thus, it is possible to mimic the conditions of complex cell interactions, such as tumor interactions, and, unlike 2D culture, it is possible to achieve greater similarity with in vivo processes. During the cell culture, a hypoxic environment will be used to simulate the oxygen depletion that occurs inside tumor masses, an important factor in triggering several cell signaling cascades. The current work brings results about the use of disintegrin DisBa-01 in 3D culture of tumor (MDA-MB-231) and endothelial cells (HUVEC) in hypoxia and normoxia environments, in order to analyze the cell migration, extracellular matrix composition and angiogenesis process under those different conditions. DisBa-01 was expressed in a heterologous system and inoculated at concentrations of 10, 100, 1000 nm in 3D cultures of MDA-MB-231, with the addition of 2000 nM’s concentration in endothelial cells, resulting in the inhibition of cell migration of tumoral cells with 100 and 1000 nM of disintegrin in both oxygen conditions, and inhibition of cell migration of endothelial cells in all concentrations in normoxia and 1000 and 2000 nM of DisBa-01 in hypoxia. The extracellular matrix components was analyzed by immunofluorescence, evidencing that the concentration of αvβ3 integrin in normoxia increased, and in hypoxia decreased, without differences in collagen type I concentration in MDA-MB-231, and the opposite effect in HUVEC, with a decrease in the integrin’s concentration in normoxia and its increase in hypoxia, with the increase of collagen type I concentration just in normoxia, with no differences in hypoxia. The in vitro angiogenesis process was performed by a HUVEC sprouting assay in normoxic conditions, which demonstrated an angiogenic blockage with the DisBa-01 disintegrin treatment, by the decrease of number and mean size of sprouts beside the control group. This work evidences promising results of the use of DisBa-01 in 3D cultures, and reinforces its antimetastatics and antiangiogenic properties.
Inhibition of αvβ3 integrin in 3D cell culture of tumor and endothelial cells in hypoxic environment using the recombinant disintegrin DisBa-01
Keywords: Integrina; Hipoxia; Câncer de mama; Integrin; Tumor microenvironment; Metastasis; Breast cancer; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR